The Fabrication and in vitro Evaluation of Retinoic Acid-Loaded Electrospun Composite Biomaterials for Tracheal Tissue Regeneration - O'Leary, Cian; Soriano, Luis; Fagan-Murphy, Aidan; Ivankovic, Ivana; Cavanagh, Brenton; O'Brien, Fergal J.; Cryan, Sally-Ann (Frontiers in Bioengineering and Biotechnology, 2020)
Although relatively rare, major trauma to the tracheal region of the airways poses a significant clinical challenge with few effective treatments. Bioengineering and regenerative medicine strategies have the potential to create biocompatible, implantable biomaterial scaffolds, with the capacity to restore lost tissue with functional neo-trachea. The main goal of this study was to develop a nanofibrous polycaprolactone-chitosan (PCL-Chitosan) scaffold loaded with a signaling molecule, all-trans retinoic acid (atRA), as a novel biomaterial approach for tracheal tissue engineering. Using the Spraybase® electrospinning platform, polymer concentration, solvent selection, and instrument parameters were optimized to yield a co-polymer with nanofibers of 181-197 nm in diameter that mimicked tracheobronchial tissue architecture. Thereafter, scaffolds were assessed for their biocompatibility and capacity to induce mucociliary functionalization using the Calu-3 cell line. PCL-Chitosan scaffolds were found to be biocompatible in nature and support Calu-3 cell viability over a 14-day time period. Additionally, the inclusion of atRA did not compromise Calu-3 cell viability, while still achieving an efficient encapsulation of the signaling molecule over a range of atRA concentrations. atRA release from scaffolds led to an increase in mucociliary gene expression at high scaffold loading doses, with augmented MUC5AC and FOXJ1 detected by RT-PCR. Overall, this scaffold integrates a synthetic polymer that has been used in human tracheal stents, a natural polymer generally regarded as safe (GRAS), and a drug with decades of use in patients. Coupled with the scalable nature of electrospinning as a fabrication method, all of these characteristics make the biomaterial outlined in this study amenable as an implantable device for an unmet clinical need in tracheal replacement.